Pharmacology Simulation Scenario: Respiratory Failure Due to Asthma Exacerbation - Jimmy Beck; Christie Romo; Kent Denmark (Association of American Medical Colleges, 2010)
Abstract This resource is a manikin-based simulation case involving a 22-year-old male who presents to an emergency room with progressive shortness of breath due to an asthma exacerbation. The patient develops respiratory failure requiring intubation during the initial emergency room treatment. This resource is one of three respiratory simulation cases developed as part of a second-year medical school pharmacology curriculum. These cases were developed to help medical students integrate basic science principles taught in traditional lectures with real-life clinical scenarios. In this scenario, the learner needs to rapidly assess a patient with an acute asthma exacerbation, describe the mechanism of action of various pharmacologic agents used in the treatment of status asthmaticus, and then determine the most likely physiologic responses after the administration of select medications. Finally, the learner must proceed to intubation of this patient after pharmacologic therapy fails. This simulation scenario has been used by approximately 180 second-year medical students. The feedback we have received has been very favorable, with many of the students requesting that we incorporate more simulation exercises into the basic science curriculum.